(untitled) (ABDIMAS: Jurnal Pengabdian Masyarakat, 2026)
Cassava tape is a traditional fermented food widely produced by household scale enterprises in Sumedang Regency; however, hygiene inconsistencies and limited fermentation control often reduce product shelf life and quality. This study aimed to evaluate the effectiveness of a community based quality management intervention in improving hygiene practices and product durability among small scale cassava tape producers. A mixed method approach based on the explanatory design of Jack R. Fraenkel and Wallen was employed, integrating quantitative and qualitative data. Five producers participated using total sampling. The intervention was conducted over three weeks and included baseline assessment, structured training, practical demonstration, and three weekly monitoring sessions. Data were collected using a 10 item Likert scale questionnaire and semi structured interviews. Quantitative data were analyzed using Microsoft Excel through descriptive statistics and a paired sample t test at a 0.05 significance level. Results showed that the mean hygiene score increased from 3.02 to 4.28, representing a 41.7 percent improvement. The paired t test indicated that the increase was statistically significant (p < 0.05). Shelf life observation further revealed an extension from three to four days to five to six days under room temperature storage. Qualitative findings supported improved awareness of contamination risks and better fermentation control. These findings suggest that structured community based quality management interventions can produce measurable and statistically supported improvements in hygiene compliance and product durability in traditional cassava fermentation systems